PENINGKATAN KOMPETENSI LITERASI DAN NUMERASI KOSENTRASI BAHASA INGGRIS DAN MATEMATIKA UNTUK ANAK - ANAK DI DESA BARU KECAMATAN PANCURBATU KABUPATEN DELI SERDANG - Simon Maruli Panjaitan; Jernih Aslina Laia; Paulina Marbun; Cumiwati Sagala; Yolanda Ginting (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This study aims to improve the English Literacy and Mathematical Numeracy skills of children in Desa Baru, Pancur Batu Sub-district, Deli Serdang Regency, conducted by students of HKBP Nommensen University Medan through the implementation of Community Service. Mathematics and English skills are becoming more important in the era of globalization, but access to good education is still a big problem in rural areas in Indonesia especially in Desa Baru. This study used descriptive quantitative research method involving 25 children aged 07-12 years old and lasted for 3 weeks (February 10-28, 2025). The results showed significant improvements in the children's competencies; progress in English literacy with a baseline average score of 59,4 and a final average of 80,4 with an average improvement of 20,6. Meanwhile, in math numeracy, the baseline average score was 54,4 and the final average was 80,8 with an average improvement of 26,4. It is evident that children can improve their skills by using learning methods such as word matching games, simple songs, flashcards and other learning approaches. This research makes an important contribution to developing useful learning strategies to improve literacy and numeracy in rural areas.